Students Qualified from Bangladesh Institute of Child Health (At present BSH&I) Vol. 37(2) - Editor, The (Dhaka Shishu (Children) Hospital Journal, 2022)
Abstract not available DS (Child) H J 2021; 37(2): 147-148